BIOETIKA DALAM HINDU - Ida Bagus Suta (DHARMASMRTI: Jurnal Ilmu Agama dan Kebudayaan, 2016)
Religion and medicine are involved when the human face the truths related to the beginning and the end of life. The reflection of the Hindu values on the issues of modernity in the medical domain must be important at least for two basic reasons: Firstly, in the philosophical sense, various Hindu schools of thought have a fascinating conformity with the demands of modern times’, the pluralistic era. And secondly, the patriarchal cultural orientation of the Balinese society on the one hand (having son is their main obligation during their marriage times) and the view of God as a personal Being (God as the creator of all) raise an ethical dilemma: in vitro fertilization (IVF).